Teknik Moderasi: Peningkatan Kualitas Pembelajaran Kaffah di UIN Mataram - Syahrial Ayub; Muhammad Taufik (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study aims to improve the quality of Kaffah learning by conducting learning evaluations with moderation techniques. The study was conducted on students at PGMI UIN Mataram. This descriptive study describes the opinions, input and suggestions of all students regarding Kaffah learning. This is an evaluation of Kaffah learning to determine its advantages and disadvantages as a reflection on further learning. The evaluation results contain current conditions, expected conditions and those responsible for solving them. Things that need attention are learning should be in the morning, occasionally outdoors, the number of tools for group work is increased to 5 to 10 groups, more games, developed on other concepts, increasing the study of the Qur'an on the concept of fluid and demonstration.